Possibilidade de inserção das mulheres nas políticas de exportação: um panorama tocantinense - Lacerda, Isabella Oliveira (Universidade Federal do Tocantins, 2023)
With the advance of globalization, the participation of women in the labor market has been increasingly significant, especially in international trade, however gender inequality and lack of opportunities have been a major obstacle for them. The present work aims to analyze the main Brazilian economic policies and the role of women in these policies, their participation in decision-making and policy creations that support women so that they can have the same opportunities as men. For this purpose, a qualitative-quantitative approach was used, as data from the Brazilian Institute of Geography and Statistics (IBGE) on the participation of women in the labor market and the National Plan of Exportculture (PNCE) in Tocantins are presented as an example of an economic policy for the entry of more women into foreign trade.